Nationalist ideas in Chile - Nes El, Moshe (Cuadernos Judaicos, 2012)
This article is about the nationalist ideas in Chile, it provides a historical context of the various presidencies and the emergence of nationalist movements in the country since the birth of the National Socialist Movement to the present day.